Pengembangan Alat Evaluasi Berbantuan Aplikasi Moodle pada Materi Teks Anekdot di Kelas X Sekolah Menengah Atas Negeri 21 Medan - Sastika Adeliah; Rika Kartika; Ratna Soraya (Medan Resource Center, 2026)
This study aimed to develop evaluation tools assisted by the Moodle application to support teachers and students in conducting assessments more quickly and effectively. The research was motivated by the need for mobile learning-based evaluation tools in Indonesian language instruction, particularly in anecdotal text material for grade X students at SMA Negeri 21 Medan. The objectives were to design the tools and to examine their validity and practicality. The study employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The participants consisted of 36 students. Quantitative data were collected through questionnaires administered to validators, yielding scores of 85% and 91% from material experts (categorized as very feasible), 92% and 90% from media experts (very feasible), 90% from the Indonesian language teacher, and 91% from students (very feasible). The validation process confirmed that the developed evaluation tools met the criteria of “very valid.” Furthermore, trial and field test results demonstrated that all test items were valid, with initial reliability categorized as low but subsequently achieving reliability during the field test phase. These findings confirm that the Moodle-assisted evaluation tools are both valid and practical for use in classroom learning.